LITERATURE STUDY ON TRANSFORMATIONAL LEADERSHIP AND ITS IMPACT ON EMPLOYEE PRODUCTIVITY IN PALM OIL COMPANY - Krismanto, Didik -; Nurcahyo, Eko Meidha; Putri, Qrizzilia Izani; Azmy, Ahmad - (Makro Jurnal Manajemen Dan Kewirausahaan, 2024)
Oil Palm Company seeks to enhance and increase its overall productivity. This study aims to explore the potential of the transformational leadership to boost employee productivity at Oil Palm Company, drawing insight from existing studies and literature. This study is to seek the contribution of transformational leadership to the improvement of the employee productivity at Oil Palm Company. The result will offer valuable insight for developing effective leadership. This Study uses qualitative research to gain a deep understanding of the relationship between the transformational leadership and employee productivity. Data collected by literature review. The findings suggest that Oil Palm Company can enhance employee productivity by implementing transformational leadership practice. This research is limited to the context of Oil Palm Company and may not be generalized to other company. This research contributes to the existing literature by providing a case study of the impact of transformational leadership productivity in Oil Palm Company.